2020
DOI: 10.1002/jia2.25553
|View full text |Cite
|
Sign up to set email alerts
|

Combating HIV stigma in low‐ and middle‐income healthcare settings: a scoping review

Abstract: Introduction Nearly 40 years into the HIV epidemic, the persistence of HIV stigma is a matter of grave urgency. Discrimination (i.e. enacted stigma) in healthcare settings is particularly problematic as it deprives people of critical healthcare services while also discouraging preventive care seeking by confirming fears of anticipated stigma. We review existing research on the effectiveness of stigma interventions in healthcare settings of low‐ and middle‐income countries (LMIC), where stigma control efforts a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 86 publications
2
35
0
Order By: Relevance
“…At the institutional level, strategies typically focus on reducing HIV stigma at healthcare settings [27,28]. An example of a community level intervention was carried out in five churches in a high HIV prevalence area of Los Angeles County, including strategies such as HIV education, pastor-delivered sermons on HIV, and HIV testing events [29].…”
Section: The Problem Of Hiv-related Stigma In Burundimentioning
confidence: 99%
“…At the institutional level, strategies typically focus on reducing HIV stigma at healthcare settings [27,28]. An example of a community level intervention was carried out in five churches in a high HIV prevalence area of Los Angeles County, including strategies such as HIV education, pastor-delivered sermons on HIV, and HIV testing events [29].…”
Section: The Problem Of Hiv-related Stigma In Burundimentioning
confidence: 99%
“…Several factors contributed to this perceived risk, including the fear of self‐contamination during care provision and fear of possible consequences of being infected. Feelings of fear and worries are common among healthcare providers during care provision to patients with HIV, mainly because they are apprehensive about the risk of self‐contamination (Athley, Binder & Mangrio 2018; Smith et al 2020). This fear results in healthcare providers' hesitance to be involved in providing care to HIV ‐affected persons or may even refrain from care provision (Garus‐Pakowska & Górajski 2019).…”
Section: Discussionmentioning
confidence: 99%
“…It is estimated that 59 000 people are living with HIV in Iran, of whom only 25 000 are on antiretroviral therapy (UNAIDS 2019). Although HIV has been around for a long time and significant advancements have been made in its treatment in the last decade, some studies have shown that there is still a significant stigma towards people living with HIV (PLWH), and the knowledge of the society of HIV infection is low, particularly in low‐ and middle‐income countries (Pudpong et al 2014; Smith et al 2020). This can adversely impact the affected people's help‐seeking behaviours and the quality of care they receive (Athley et al, 2018; Duby et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations